2020
DOI: 10.1136/jech-2019-212368
|View full text |Cite
|
Sign up to set email alerts
|

Global systematic review of the effects of suicide prevention interventions in Indigenous peoples

Abstract: ObjectiveSuicide rates are often higher in Indigenous than in non-Indigenous peoples. This systematic review assessed the effects of suicide prevention interventions on suicide-related outcomes in Indigenous populations worldwide.MethodsWe searched CINAHL, Embase, PubMed, PsycINFO, ProQuest Dissertations & Theses and Web of Science from database inception to April 2020. Eligible were English language, empirical and peer-reviewed studies presenting original data assessing the primary outcomes of suicides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…As in our review, Clifford et al (2013), Harlow et al (2014) reported favourable outcomes and limited high-quality evaluations of such interventions, with few studies employing experimental designs suggesting a need for more high-quality evidence to demonstrate intervention effectiveness. Similar conclusions were drawn by Leske et al (2020).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As in our review, Clifford et al (2013), Harlow et al (2014) reported favourable outcomes and limited high-quality evaluations of such interventions, with few studies employing experimental designs suggesting a need for more high-quality evidence to demonstrate intervention effectiveness. Similar conclusions were drawn by Leske et al (2020).…”
Section: Discussionsupporting
confidence: 87%
“…Clifford et al (2013) suggested that cultural adaptations or tailoring may increase acceptability to Indigenous peoples, and in our review, we observed varying degrees of cultural adaptations or centering, but also tailoring to increase study feasibility. Among our 10 studies, 9 were included in the review by Leske et al (2020) which had 24 studies. Our tenth study was published in 2020.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… [34 , 49 , 53] For example, the gender roles and expectations placed upon young women in Indian-Fijian households, [5 , 37] the unique challenges of young people, [5 , 7 , 19] and the cultural preferences of Indigenous peoples. [66] For young people, these strategies could include further means restriction, awareness and skills training, and gatekeeper training programs with schools. [14] Interestingly, gender associations with suicidal behaviours were not as clear as in other Western Pacific countries such as Australia or New Zealand whereby there is a clear preponderance of suicide in men and suicide attempts in women.…”
Section: Discussionmentioning
confidence: 99%